Pegaruh Good Corporate Governance Terhadap Kinerja Penisahaan - Nur Fauziah; Hidayatur Rahman (Jurnal Aplikasi Bisnis, 2017)
Tbis study aims to analysre the effect ofgood corporate governance to company perfomance. GCG ivas measured by using corporate governance perception index (CGPl), which is based on a ranking that has been compiled by the Indonesian Institute of Corporate Governance (IICG). Company performance is assessed by Value Return on Equity (ROE) and Tobins'Q, The statistical method used is multiple regression analysis. The data used in this study is secondary data fiom SWA magazine and the company's financial statements obtained from the Indonesian Capital Market Directory (ICA'LD) starting from the year2005-2008.Based on the results of hypothesis testing using the test statistic t-test (with a confidence level of 95% and ct —5%) can be concluded that: First, good coporate governance index is not significantly effect ROE. Second, the index ofthe GCG has no significant ffect on Tobins'Q. This shows that good corporate governance index is still not able to describe properly the performance of companies in Indonesia.